The use of aspirin for primary prevention of cardiovascular disease is associated with a lower likelihood of COVID‐19 infection - Merzon, Eugene; Green, Ilan; Vinker, Shlomo; Golan‐Cohen, Avivit; Gorohovski, Alessandro; Avramovich, Eva; Frenkel‐Morgenstern, Milana; Magen, Eli (The FEBS journal, 2021)
Acetylsalicylic acid (aspirin) is commonly used for primary and secondary prevention of cardiovascular diseases. Aspirin use is associated with better outcomes among COVID‐19 positive patients. We hypothesized that the aspirin use for primary cardiovascular disease prevention might have a protective effect on COVID‐19 susceptibility and disease duration. We conducted a retrospective population‐based cross‐sectional study, utilizing data from the Leumit Health Services database. The proportion of patients treated with aspirin was significantly lower among the COVID‐19‐positive group, as compared to the COVID‐19‐negative group [73 (11.03%) vs. 1548 (15.77%); P = 0.001]. Aspirin use was associated with lower likelihood of COVID‐19 infection, as compared to nonusers (adjusted OR 0.71 (95% CI, 0.52 to 0.99; P = 0.041). Aspirin users were older (68.06 ± 12.79 vs. 56.63 ± 12.28 years of age; P < 0.001), presented a lower BMI (28.77 ± 5.4 vs. 30.37 ± 4.55; P < 0.0189), and showed higher prevalence of hypertension (56, 76.71%), diabetes (47, 64.38%), and COPD (11, 15.07%) than the aspirin nonusers (151, 25.64%, P < 0.001; 130, 22.07%, P < 0.001; and 43, 7.3%, P = 0.023, respectively). Moreover, COVID‐19 disease duration (considered as the time between the first positive and second negative COVID‐19 RT–PCR test results) among aspirin users was significantly shorter, as compared to aspirin nonusers (19.8 ± 7.8 vs. 21.9 ± 7.9 P = 0.045). Among hospitalized COVID‐positive patients, a higher proportion of surviving subjects were treated with aspirin (20, 19.05%), as opposed to 1 dead subject (14.29%), although this difference was not significant (P = 0.449). In conclusion, we observed an inverse association between the likelihood of COVID‐19 infection, disease duration and mortality, and aspirin use for primary prevention. Acetylsalicylic acid (aspirin) is used for the prevention of cardiovascular diseases and might be associated with better outcomes among COVID‐19 patients. We hypothesized that aspirin use for primary cardiovascular disease prevention might have effects on COVID‐19 susceptibility. We conducted a retrospective population‐based study, utilizing data from the Leumit Health Services database. We observed an inverse association between the likelihood of COVID‐19 infection, disease duration and mortality, and aspirin use for primary prevention.